THE INFLUENCE OF SOCIAL MEDIA MARKETING ACTIVITIES, CUSTOMER EXPERIENCE ON REPURCHASE INTENTION THROUGH RELATIONSHIP QUALITY IN INDONESIAN E-COMMERCE - Ari Anggarani; Angga Sepian Kusnanda (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
This study examines the influence of social media marketing activities and customer experience on repeat purchase intention through relationship quality in the context of e-commerce in Indonesia. The main purpose of the study is to test the direct and indirect relationship between these variables. By involving 190 respondents of e-commerce users and using the SEM PLS method, the results showed that both social media marketing activities and customer experience had a positive influence on the quality of relationships, which in turn had a positive effect on repeat purchase intentions. In addition, relationship quality was found to mediate the influence of social media marketing activities and customer experience on repeat purchase intent. These findings provide new insights into the factors influencing repurchase intent in the context of e-commerce in Indonesia.